Acute coronary syndrome (unstable angina and non-ST elevation MI) - Sarkees, Michael L (BMJ Publishing Group, 2009)
INTRODUCTION: In people with acute coronary syndrome (ACS) the incidence of serious adverse outcomes (such as death, acute myocardial infarction [MI], or refractory angina requiring emergency revascularisation) is 5-10% within the first 7 days and about 15% at 30 days. Between 5-14% of people with acute coronary syndrome die in the year after diagnosis, with about half of these deaths occurring within 4 weeks of diagnosis. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of: antiplatelet; antithrombin; anti-ischaemic; lipid-lowering; and invasive treatments? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2007 (Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 32 systematic reviews, RCTs, or observational studies that met our inclusion criteria. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: aspirin, beta-blockers, calcium channel blockers, clopidogrel, direct thrombin inhibitors, glycoprotein IIb/IIIa inhibitors (oral or intravenous), heparin (low molecular weight, unfractionated), nitrates, routine early cardiac catheterisation and revascularisation, statins, and warfarin.